Evaluation of actual and estimated hydraulic conductivity of sands with different gradation and shape - Akbulut, Nurullah; Cabalar, Ali Firat (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
Hydraulic conductivities of sands with different gradation and grain shape were estimated experimentally at a relative density (D-r) of about 40 % and a 22 +/- 2 degrees C of constant temperature. Narli Sand (NS) with 0.67 of sphericity (S) and 0.72 of roundness (R), and Crushed Stone Sand (CSS) with 0.55 of S and 0.15 of R values were artificially graded into sixteen different grain-size fractions (4.75-2,2-1.18, 1.18-0.6, 0.6-0.425, 0.425-0.3, 0.3-0.075, 4.75-0.075,2-0.075, 1.18-0.075, 0.6-0.075, 0.425-0.075, 4.75-0.6, 2- 0.6, 4.75- 0.425, 2- 0.425, 1.18- 0.425 mm). Hydraulic conductivities of the NS estimated by use of constant head test ranged from 1.61 to 0.01 cm/s, whilst those of the CSS estimated by the same test ranged from 2.45 to 0.012 cm/ s. It was observed that the hydraulic conductivity values of the NS are lower than those of the CSS samples, which is likely to be the result of differences in shape, particularly in R values. The results clearly demonstrated that the hydraulic conductivity can be significantly influenced by grading characteristics ( d(10), d(20), d(30), d(50), d(60), c(u), c(C), n, I-O). Furthermore, comparisons between results obtained in the present study and hydraulic conductivity estimated with other formulas available in the literature were made. The comparisons indicated that the best estimation of hydraulic conductivity changes based on the gradation and shape properties of the sands tested.
Keywords: Hydraulic conductivity; Sand; Gradation; Shape